Manuscript Carriers and Their Impact on the Transmission of Narratives from the 1st to the 3rd Century AH - Ayadi, Hassina; Rahmoun, Abdelkader; Mohamed, Rami Sidi (Journal of Ecohumanism, 2026)
The task of recording texts during the early stages of Arab-Islamic civilization constituted a major challenge. Although written texts at this stage were initially limited to the Holy Qur’an and the Prophetic Hadith, they soon expanded in scope and volume to include the sayings of the Companions and, shortly thereafter, those of the Successors. This expansion necessitated the use of writing materials known as manuscript media, which were primitive in their early forms—such as parchment, bones, and palm ribs—before gradually evolving alongside the territorial expansion of the Islamic world. Influenced by the outcomes of neighboring civilizations, these media ultimately culminated in the adoption of paper, which proved most suitable for the documentation of sciences by the third Hijri century.Parallel to this material development emerged a methodological process of equal importance, known as the methods of transmitting narrations. These methods aimed to enhance the reliability of scholarly transmission and consequently underwent significant diversification and development. This study seeks to reveal the relationship between the evolution of manuscript media and their impact on the development of methods of transmitting narrations within Arab-Islamic civilization during its first three centuries.The study concludes that the challenge of developing methods of narration transmission in Arab-Islamic civilization interacted positively with the advancement of manuscript media. Together with the system of isnād (chain of transmission) and the sciences of al-jarḥ wa al-taʿdīl (narrator criticism and validation), this interaction achieved an exceptionally high level of reliability and trustworthiness. Such rigor ensured the preservation of the Qur’anic text and the noble Prophetic Hadith—the two foundational pillars of Islamic civilization—and subsequently safeguarded the transmission of scholarly opinions and narrations across various scientific disciplines.